Risk Factors for Multiple Sclerosis in Children - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2011)
Risk factors for multiple sclerosis in 302 children presenting with CNS demyelination to health-care facilities in Canada included HLA-DRB1*15 alleles, previous infection with Epstein-Barr virus, and low serum 25-hydroxyvitamin D.